2010
DOI: 10.1136/oem.2010.056739
|View full text |Cite
|
Sign up to set email alerts
|

Participatory ergonomics to reduce exposure to psychosocial and physical risk factors for low back pain and neck pain: results of a cluster randomised controlled trial

Abstract: ISRCTN27472278.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 39 publications
0
37
0
1
Order By: Relevance
“…This finding may suggest that the provision of lifting equipment positively impacts nurses' control over job tasks, or alternatively that the provision of lifting equipment by the employer is the result of the nurses' high control over their working conditions. Driessen et al (2011) found that a participatory, ergonomic intervention significantly increased job control. Improved job control reduces job strain-which has implications for musculoskeletal, cardiovascular, and mental health outcomes (Sultan-Taieb et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…This finding may suggest that the provision of lifting equipment positively impacts nurses' control over job tasks, or alternatively that the provision of lifting equipment by the employer is the result of the nurses' high control over their working conditions. Driessen et al (2011) found that a participatory, ergonomic intervention significantly increased job control. Improved job control reduces job strain-which has implications for musculoskeletal, cardiovascular, and mental health outcomes (Sultan-Taieb et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…A previous analysis conducted on the data of this study showed that, after six months, PE generally failed to statistically significantly reduce workers' exposure to the perceived physical and psychosocial risk factors for LBP and NP. Improvements due to PE were only found on decision authority and latitude (36) and even these were not sustained beyond the 12-months of follow-up (data not shown).…”
Section: Explanation Of the Findingsmentioning
confidence: 99%
“…Dyrbye et al (2006) confirmed that despite the notion that burnout is mainly linked to work-related stress, a strong relationship also exists between personal life events and professional burnout—highlighting the importance of investigating both job and personal demands in creating a better understanding of burnout as experienced by employees. The impact of job demands on burnout has been explored by various researchers (e.g., Alarcon, 2011; Seidler et al, 2014), and typically include aspects such as work overload, emotional demands, mental demands, work–home interference, role ambiguity, role conflict, role stress, stressful events, and time pressure (Olivares-Faúndez, Gil-Monte, Mena, Jélvez-Wilke, & Figueiredo-Ferraz, 2014; Lee & Ashforth, 1996; Peeters, Montgomery, Bakker, & Schaufeli, 2005; Schaufeli, Bakker, & Van Rhenen, 2009). In investigating the impact of life demands on burnout, life events have been found to have an impact on burnout risk, e.g., divorce, personal illness, illness or death of a close family member, marriage, birth, and adoption of a child (Dybre et al, 2006).…”
Section: Introductionmentioning
confidence: 99%